The Nature and Causes of Chronic Obstructive Pulmonary Disease: A Historical Perspective - C Peter W Warren (Canadian Respiratory Journal)
Chronic obstructive pulmonary disease (COPD) is the currently favoured name for the diseases formerly known as emphysema and bronchitis. COPD has been recognized for more than 200 years. Its cardinal symptoms are cough, phlegm and dyspnea, and its pathology is characterized by enlarged airspaces and obstructed airways. In the 19th century, the diagnosis of COPD depended on its symptoms and signs of a hyperinflated chest, and reduced expiratory breath sounds. The airflow obstruction evident on spirometry was identified in that century, but did not enter into clinical practice. Bronchitis, and the mechanical forces required to overcome its obstruction, was believed to be responsible for emphysema, although the inflammation present was recognized. The causes of bronchitis, and hence emphysema, included atmospheric and domestic air pollution, as well as dusty occupations. Cigarette smoking only became recognized as the dominant cause in the 20th century. The lessons learned of the risks for COPD in 19th-century Britain are very pertinent to the world today.